Research anthology on concepts, applications, and challenges of FinTech (Business Science Reference, IGI Global, 2021)
"This book of contributed chapters covers the latest technologies in FinTech with a comprehensive view of the impact on the industry, where these technologies are implemented, how they are improving financial services, and the security applications and challenges being faced"--